ISOLATION, SCREENING, CHARACTERIZATION AND ANTAGONISM ASSAY OF PGPR ISOLATES FROM RHIZOSPHERE OF BT AND NON BT COTTON PLANTS - A.B. RAJITHASRI,; K. SATYAPRASAD, (International Journal of Pharma and Bio Sciences, 2015)
Plant growth-promoting rhizobacteria (PGPR) are beneficial bacteria that colonize plant roots and enhance plant growth by a wide variety of mechanisms. The use of PGPR is steadily increasing in agriculture and offers an attractive way to replace chemical fertilizers, pesticides, and supplements. In our investigation, we have isolated, screened and characterized the PGPR from the rhizosphere soil of Bt and non Bt cotton, were collected from different areas of Khammam and Warangal districts in Telangana, India. Bacterial isolates were screened preliminarily for their antifungal activity against Colletotrichum gossypi, Fusarium oxysporum, Macrophomina phaseolina and Rhizoctonia solani. 23 antagonistic isolates were tested for their PGP traits, extra cellular enzyme and siderophore production. The present study, suggests that the use of PGPR isolates as inoculants/ biofertilizers might be beneficial for cotton cultivation as they enhanced growth of cotton due to the production of IAA, NH3, phosphate solubilization, siderophore production and also having antifungal activity against phytopathogenic fungi.